Features of uneasiness at emotionally steady and unstable kickboxing - Павлик, О. М.; Вакуленко, Д. О. (Slobozhanskyi Herald of Science and Sport, 2011)
It is revealed indicators of jet and situational uneasiness at emotionally steady and unstable kickboxing.